The Analysis of Slang Variation and Emotional Expression in Selected Song Lyrics by Billie Eilish[ - Sinta Elsalina Sinulingga; Arsen Nahum Pasaribu; Rotua Elfrida Pangaribuan (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2026)
This study analyzes slang variation and emotional expression in selected song lyrics by Billie Eilish using sociolinguistic and pragmatic approaches. Previous studies have generally examined slang usage and emotional expression separately, with limited attention to how slang contributes to emotional meaning construction in contemporary popular music. This study addresses that gap by investigating the relationship between slang variation, emotional expression, and identity representation in Billie Eilish’s lyrics. The study also contributes theoretically by integrating sociolinguistic theories of slang with pragmatic analysis of emotional meaning. This research employs a qualitative descriptive method with data collected from nine selected songs: “Bad Guy,” “Bury a Friend,” “Therefore I Am,” “Lost Cause,” “Your Power,” “Happier Than Ever,” “My Strange Addiction,” “idontwannabeyouanymore,” and “Six Feet Under.” The findings reveal three types of slang: General Slang (45%), Creative Slang (32.5%), and Group Slang (22.5%). General Slang is dominant because it creates conversational authenticity and emotional closeness with listeners. The emotional expressions identified include sadness (30%), anger (22.5%), fear or anxiety (17.5%), frustration (12.5%), insecurity (7.5%), emotional vulnerability (5%), and confidence or rebellion (5%). The findings demonstrate that slang functions not only as informal language but also as a sociolinguistic and pragmatic strategy for intensifying emotional meaning, expressing identity, and representing youth culture in contemporary song lyrics.